2021
DOI: 10.1111/tbed.14224
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of chronic Q fever and chronic fatigue syndrome: A 6 year follow‐up of a large Q fever outbreak

Abstract: Acute Q fever is a generally self-limiting infection caused by the intracellular gramnegative bacterium Coxiella burnetii. For yet unknown reasons, a subset of patients develops chronic infection. Furthermore, chronic fatigue syndrome (CFS) as post-acute Q fever sequelae has been described. We here investigated the rates of chronic Q fever and incidences of CFS 6 years after one of the largest European Q fever outbreaks that occurred in Jena, Germany in 2005 with 331 reported cases, who lived in proximity of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…Moreover, in yet another Q fever outbreak involving a UK cohort of slaughterhouse workers, ME/CFS criteria were fulfilled by 28% of participants 5-14 years after Q fever but by none of the matched controls 77 . In contrast, a recent study from Germany found a significantly higher frequency of unrefreshing sleep, but not of other typical post-acute features, in cases relative to seronegative household contacts 6 years after Q fever, on the basis of assessments by the Short Form Symptom Inventory questionnaire 78 . This result suggests that assessment methods and the choice of appropriate questionnaire might play an important role in ascertaining infection-associated chronic disability.…”
Section: Clinical Case Definitionsmentioning
confidence: 62%
See 1 more Smart Citation
“…Moreover, in yet another Q fever outbreak involving a UK cohort of slaughterhouse workers, ME/CFS criteria were fulfilled by 28% of participants 5-14 years after Q fever but by none of the matched controls 77 . In contrast, a recent study from Germany found a significantly higher frequency of unrefreshing sleep, but not of other typical post-acute features, in cases relative to seronegative household contacts 6 years after Q fever, on the basis of assessments by the Short Form Symptom Inventory questionnaire 78 . This result suggests that assessment methods and the choice of appropriate questionnaire might play an important role in ascertaining infection-associated chronic disability.…”
Section: Clinical Case Definitionsmentioning
confidence: 62%
“…Prospective cohort van Loenhout 183 , Wildman 74 , Ayres 75 , Ankert 78 , Hickie 31 , Hatchette 184 Case-control Ayres 73 , Marmion 77 , van Woerden 76 Cross-sectional Bronner 79 Case report Leung-Shea 185…”
Section: Coxiella Burnetiimentioning
confidence: 99%
“…Most of those affected with acute Q-fever, recover from fatigue within 6 to 12 months (4). Approximately 20% does not recover within this timeframe, leading to Q-fever Fatigue Syndrome (QFS) diagnosis (4,7). QFS has been associated with immune deregulation (8) and possibly mitochondrial dysfunction (9), however the aetiology and pathophysiology of QFS is still largely unknown (8,9).…”
Section: Introductionmentioning
confidence: 99%
“…Most of those affected with acute Q-fever recover from fatigue within 6 to 12 months [4]. Approximately 20% does not recover within this timeframe, leading to Q-fever fatigue syndrome (QFS) diagnosis [4,7]. QFS has been associated with immune deregulation [8] and possibly mitochondrial dysfunction [9]; however, the etiology and pathophysiology of QFS is still largely unknown [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…The term QFS is derived from chronic fatigue syndrome (CFS), also known as myalgic encephalomyelitis (ME), because of its similar expression. Like with CFS/ ME, individuals with QFS have, in addition to severe fatigue, a complex set of symptoms including, e.g., headache, muscle and/or joint strains, sore throat, and painful lymph nodes [6,7,10]. Post exertional malaise, unrefreshing sleep, memory or concentration difficulties, and issues regarding mental well-being, are also common [6,7,10].…”
Section: Introductionmentioning
confidence: 99%